2010
DOI: 10.4103/0250-474x.62236
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of some cameroonian plants extracts used in the treatment of intestinal and infectious diseases

Abstract: Antioxidant activity test using two different methods namely 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azinobis(3-ethylbenzothialozinesulfonate) diammonium salt free radical scavenging test has been carried out on three Cameroonian plant extracts used in the treatment of intestinal and infectious diseases: Pittosporum mannii Hook f. (Pittosporaceae), Vepris heterophylla R. Letouzey (Rutaceae) and Ricinodendron heudelotii (Baill) Pierre ex Pax (Euphorbiaceae). Results of this study in the 2,2-diphenyl-1-picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Previously, the antibacterial activity of leaves extract of Pittosporum viridiflorum against Enterobacter aerogenes, E. coli, Proteus vulgaris, Bacillus cereus, and Salmonella typhi was recorded by Swamy et al [23] The extract was active against all the other organisms except S. typhi, and zones of inhibition were observed to be much similar to the present study. The same results of antioxidant activity of Pittosporum mannii Hook f. were reported by Momeni et al [24] TPC, TFC, and antioxidant potential of Pittosporum dasycaulon Miq. were reported by Mani and Dennis.…”
Section: Antimicrobial Activitysupporting
confidence: 87%
“…Previously, the antibacterial activity of leaves extract of Pittosporum viridiflorum against Enterobacter aerogenes, E. coli, Proteus vulgaris, Bacillus cereus, and Salmonella typhi was recorded by Swamy et al [23] The extract was active against all the other organisms except S. typhi, and zones of inhibition were observed to be much similar to the present study. The same results of antioxidant activity of Pittosporum mannii Hook f. were reported by Momeni et al [24] TPC, TFC, and antioxidant potential of Pittosporum dasycaulon Miq. were reported by Mani and Dennis.…”
Section: Antimicrobial Activitysupporting
confidence: 87%
“…ex Schult. It has been reported that phenolics inactivate iron ions by chelating and additionally suppressing the superoxide-driven Fenton reaction, which is believed to be the most important source of reactive oxygen ions [44]. The results from this study suggest that high phenolic content in cultivated A. amatymbica could have pharmacological effects which may also be attributed to agromorphological divergence.…”
mentioning
confidence: 59%
“…Its seeds are also used as food ingredient [16]. R. heudelotii is well documented for some pharmacological properties among which antimicrobial [18, 19] and antioxidant activities [20]. In the continuous search for antibacterial agents from that plant, we have designed this study to investigate the in vitro antibacterial and antibiotic resistance modulating activities of the methanol extracts from leaves and stem bark of R. heudelotii against MDR Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%